A peer support intervention for first-time mothers: Feasibility and preliminary efficacy of the mummy buddy program. Issue 6 (November 2021) - Law, K.H.; Dimmock, J.A.; Guelfi, K.J.; Nguyen, T.; Bennett, E.; Gibson, L.; Tan, X.H.; Jackson, B.
Abstract: Background: The transition to motherhood, although joyous, can be highly stressful, and the availability of professional postpartum support for mothers is often limited. Peer volunteer support programs may offer a viable and cost-effective method to provide community-based support for new mothers. Aim: To determine the feasibility of a peer volunteer support program— The Mummy Buddy Program —in which experienced volunteer mothers are paired with, and trained to offer social support to, first-time mothers. Methods: Using a single-group non-randomised feasibility trial, a total of 56 experienced mothers participated in the Mummy Buddy training program, which was focused on education and practical exercises relating to the provision of various forms of social support. Experienced mothers ('Mummy Buddies') were subsequently paired with expectant first-time mothers ( n  = 47 pairs), and were encouraged to provide support until 24-weeks postpartum. Findings: In terms of key feasibility considerations, 95.1% of Mummy Buddies felt that they were trained sufficiently to perform their role, and 85.8% of New Mothers were satisfied with the support provided by their Buddy. Analyses of preliminary efficacy (i.e., program outcomes) revealed that the first-time mothers maintained normal levels of stress and depressive symptomology, and possessed relatively strong maternal functioning, across the program duration. Conclusion: The Mummy Buddy Program appears to be a feasible and potentially valuable peer volunteer support program for first-time mothers. This study provides a foundation for program expansion and for work designed to examine program outcomes—for first-time mothers, Mummy Buddies, and entire family units—within a sufficiently-powered randomised controlled trial.